2021
DOI: 10.1186/s12888-021-03292-1
|View full text |Cite
|
Sign up to set email alerts
|

Altered spontaneous neural activity in the precuneus, middle and superior frontal gyri, and hippocampus in college students with subclinical depression

Abstract: Background Subclinical depression (ScD) is a prevalent condition associated with relatively mild depressive states, and it poses a high risk of developing into major depressive disorder (MDD). However, the neural pathology of ScD is still largely unknown. Identifying the spontaneous neural activity involved in ScD may help clarify risk factors for MDD and explore treatment strategies for mild stages of depression. Methods A total of 34 ScD subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 76 publications
3
35
1
Order By: Relevance
“…These are consistent with the results of our study. However, findings that are inconsistent with ours were reported, including those those in the study of Zhang et al (2021) where it was shown that ReHo in the right precuneus lobe of patients with SA depression was significantly increased compared with healthy controls. Studies reported that relative to patients with LOD (later adult onset depression, age 30–44), patients with EOD (early adult onset depression, age 18–29) displayed significantly increased ReHo in the left precuneus ( Chen et al, 2012 ; Shen et al, 2017 ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These are consistent with the results of our study. However, findings that are inconsistent with ours were reported, including those those in the study of Zhang et al (2021) where it was shown that ReHo in the right precuneus lobe of patients with SA depression was significantly increased compared with healthy controls. Studies reported that relative to patients with LOD (later adult onset depression, age 30–44), patients with EOD (early adult onset depression, age 18–29) displayed significantly increased ReHo in the left precuneus ( Chen et al, 2012 ; Shen et al, 2017 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Another study ( Modinos et al, 2014 ) found that the volume of anterior cingulate gyrus negatively correlated with suicidal symptoms. The correlation analysis of another study ( Zhang et al, 2021 ) showed that there was no significant correlation between the BDI-II score and the ReHo value of the precuneus in the SA group. Our study found that the mean ReHo in the right cingulate gyrus was correlated with HAMD-SA scores, but was not associated with HAMD-24 scores.…”
Section: Discussionmentioning
confidence: 90%
“…As an important part of the prefrontal cortex ( Li et al, 2013 ), the left superior frontal gyrus plays a vital role in self-awareness ( Niendam et al, 2012 ) and negative emotion regulation ( Chen et al, 2022 ), and it is involved in attention control and emotion regulation in patients with MDD ( Dutta et al, 2014 ; Hamilton et al, 2015 ). In this study, we found that patients with MDD had significantly lower ALFF in the left superior frontal gyrus than healthy controls, which is consistent with the findings of previous studies ( Liu et al, 2020 ; Zhang et al, 2021 ). The decreased spontaneous activities of brain neurons in the superior frontal gyrus may lead to low mood, anhedonia, and excessive negative self-evaluation in patients with MDD ( Guo et al, 2013 ).…”
Section: Discussionsupporting
confidence: 93%
“…The number of depressive episodes has a significant positive correlation with the ALFF in the precuneus ( Jing et al, 2013 ). The present study demonstrated that patients with MDD had significantly higher ALFF in the left precuneus than healthy controls, indicating an excessive increase and abnormal activation of neuronal activities in this brain region of these patients; this finding is consistent with the that of previous studies ( Guo et al, 2013 ; Yao et al, 2014 ; Zhang et al, 2021 ) and may be associated with a stronger negative self-awareness and sensory dysfunction ( Gong et al, 2020 ; Wang et al, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…Atrophy occurs as a consequence of an increase in glucocorticoid levels due to the alteration of the hypothalamic-pituitary-adrenal (HPA) axis [ 35 ]. Moreover, it has been proven that functional and structural changes in this brain region lead to abnormal emotional processing and defective cognition [ 36 ].…”
Section: Major Depressive Disorder In Womenmentioning
confidence: 99%